Use of Mobile Device Apps in Virtual Courses by English as a Foreign Language (EFL) University Students - Romero-Argueta, Jesús; Coreas-Flores, Edwin Osmil; Sura-Majano, Osmin (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study investigates the use of mobile device applications for English language learning among university students enrolled in virtual EFL (English as a Foreign Language) courses in El Salvador. Adopting a descriptive, quantitative, and relational research design, data were collected from 199 students across all academic levels within an English language bachelor’s program. Findings reveal that nearly half of the students report an intermediate level of engagement with mobile apps for English learning. However, a notable portion of students do not utilize entertainment-based language learning apps, indicating selective use based on perceived educational value. Statistical analysis shows a significant variation in app usage by academic level, with advanced students demonstrating higher engagement. No significant difference was found based on gender. These results reflect increasing digital competence among university students and emphasize the importance of providing targeted support and structured integration of mobile learning tools within virtual EFL curricula to enhance language acquisition outcomes.